The routing problem for school buses considering accessibility and equity. (June 2022) - Liu, Zhongshan; Gang, Longhui; Yu, Bin; Zhang, Hexin
Abstract: School bus services play an important role in the daily commuting of students in small cities. In this paper, we research the school bus routing problem in Holingol, in which the accessibility of schools and the equity of schemes are considered. We measure the accessibility of schools by the average commuting time of students and the equity of schemes by the average detour time of students. The results show that applying the transfer strategy to solve the proposed problem can reduce the number of required school buses. Assigning more school buses to implement the second step of transfer strategy is conductive to improving the quality of solutions. Besides, the detour time for students is reduced to guarantee the equity of schemes. The findings highlight that policy makers should consider the long detour time of students and design schemes to overcome the observed inequity in small cities.